#WhyWeDoResearch: Raising research awareness and opportunities for patients, public and staff through Twitter. (21st February 2019) - Yhnell, Emma; Smith, Hazel; Walker, Kay; Whitehouse, Claire
Abstract : The #WhyWeDoResearch campaign was set up in 2014 and was originally planned to run locally, in Norfolk, at the James Paget University Hospitals NHS Foundation Trust (JPUH) for 12 days in December. Within four days, the campaign was being utilized nationally by other trusts and charities. By the New Year of 2015 it became international and had reached Australia and Canada. The intended audience for the campaign is broad and includes: patients, the general public, all staff working in health care and/or research including (but not limited to) National Health Service (NHS), commercial companies, charities and schools. The campaign has become a community where patients, staff and public alike can share their voices about health research on an equal playing field. Each year, to coincide with International Clinical Trials Day (ICTD) on 20 May, a #WhyWeDoResearch 'Tweetfest' is hosted. This includes a number of 'tweetchats' at set times throughout the Tweetfest. Tweetchats are hosted by experts in particular diseases or other areas. Patients and patient groups are included in this group of experts. This article uses the #WhyWeDoResearch campaign annual Tweetfest to demonstrate how social media can be utilized to raise awareness of health research around the world.